CLASSIFICATION OF COLOUR –BASED METAPHORICAL TERMS - Iljinska, Larisa; Platonova, Marina (Vertimo studijos, 2017)
The nature of the contemporary technical text has been changing. Traditional conventions of technical text production are not strictly observed, and the boundaries between styles and genres are becoming blurred. The tendencies in the development of technical text have caused changes in the development of technical vocabulary, initiating the on-going process of metaphorization and an extension of meaning of the existing and newly created terms.The present article mainly aims at the analysis of the tendency for metaphorization of technical terms and at the elaboration of the classification of the colour-based metaphorical terms. The pattern of the colour-based term creation is frequently applied to denote the emerging concepts. The complicated mechanisms underlying the processes of meaning formation, extension or compression are illustrated in the article considering the colour-based ESP terms in English and their possible translation into Latvian.